Feasibility and Safety of Renal and Visceral Target Vessel Cannulation Using Robotically Steerable Catheters During Complex Endovascular Aortic Procedures. (April 2015) - Cochennec, Frédéric; Kobeiter, Hicham; Gohel, Manj; Marzelle, Jean; Desgranges, Pascal; Allaire, Eric; Becquemin, Jean Pierre
Purpose: To evaluate the safety and success of target vessel cannulation in the visceral aortic segment using the Magellan robotic catheter system (RCS) during complex endovascular aortic procedures.Methods: Robotic navigation was attempted for access to 37 target vessels in 15 patients (14 men; mean age 75±10 years) during 16 fenestrated and/or branched stent-grafting procedures and 1 endovascular repair requiring the chimney technique. For each target vessel, robotic navigation was attempted for a maximum of 15 minutes; if cannulation was unsuccessful in that time, manual catheters were employed. Safety was evaluated by recording intraoperative adverse events, intraoperative complications related to robotic navigation, and postoperative complications. Technical success of robotic cannulation, wire cannulation times, and times for inserting the leader over the wire in the target vessels were recorded to assess RCS performance.Results: Successful robotic cannulation was achieved for 30 (81%) of the 37 target vessels, with a median wire cannulation time of 263 seconds (range 40–780) and a median 15 seconds (range 5–450) for inserting the leader over the wire. No intraoperative complications related to robotic navigation were observed. Seven of 27 arteries accessed via 7 fenestrations could not be cannulated within 15 minute s ; all were cannulated successfully using conventional catheters (mean cannulation time 31±7 minutes). All 10 target vessels accessed via branches and chimney stents were successfully cannulated with the RCS.Conclusion: Cannulation of target vessels with the RCS during complex endovascular aortic procedures is feasible and safe. The robotic system was particularly effective for branched and chimney stents.